Modeling of bond between near-surface mounted CFRP laminate strips and concrete - Sena-Cruz, José (2004)
Near-surface mounted (NSM) laminate strips of carbon fiber reinforced polymer (CFRP) is a promising technique for increasing the flexural and the shear strength of deficient concrete members. Using the results of an experimental program with pullout-bending tests and developing a numerical strategy, an analytical bond stress–slip relationship was obtained. This relationship was converted into a bond stress–slip constitutive law for a line interface finite element, used to simulate the concrete–CFRP bond behavior. The numerical model developed predicted all the significant aspects registered experimentally, and can be used to assess relevant information in the design of concrete structures strengthened by NSM technique.